Strategic Thinking in Arthashastra and its Corporate Relevance: An Exploration of Ancient Indian Wisdom for Modern Business - Jain, Gunjan (Ushus Journal of Business Management, 2025)
The modern corporate prospect, characterized by volatility, diversity, and ethical analysis, gradually demands to go through the principles for sustainable success. This paper aims to study the impact of strategic management principles of Kautilya’s Arthashastra and their relevance to prevailing corporate systems. This paper inspects the direct applicability of its core principles - such as the Saptanga, which stands for seven limbs of the state, Shadgunya, which stands for six-fold foreign policy, and principles of Yogakshema, which stands for welfare and scrutiny – to new era corporate leadership, governance, strategic formulation, sustainability practices, and ethical work environment. Moreover, this paper demonstrates how age-old philosophies - Arthashastra within the larger framework of Indian philosophical traditions, including the Vedas, Upanishads, and Bhagavad Gita inform and enrich current business practices. A qualitative analysis including tabular representation of Arthashastric principles and their corporate applications has been conducted highlighting the impact on key business areas. The implementation of these principles is examined through conceptual analysis of India’s leading conglomerate i.e. The Tata Group, indicating ESG (Environmental, Social, Governance) Performance Metrics along with its comparative analysis of Stakeholder Trust Metrics, in this paper.